Reconciling the monumental and the everyday : reconsidering monumentality, memory, and identity in the City of Tshwane's transient urban landscape - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.